Perencanaan pembelajaran fase A dalam implementasi kurikulum merdeka di sekolah dasar - Vitalia Januarti; Sri Marmoah; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2023)
This study aims to describe learning planning in the implementation of the independent curriculum. This study uses a descriptive-qualitative approach. The results of teacher and principal interviews, planning observations, and documentation became the data in this study. Data collection techniques using the methods of observation, interviews, and documentation Data validity using the triangulation. technique. Data analysis techniques use data collection, data reduction, data presentation, and data conclusions. The results of this study show that learning planning is important so that learning can run systematically. Teacher learning planning is involved in the implementation of the independent curriculum, namely the formulation of learning objectives, the preparation of learning objectives flows, and the preparation of teaching modules. The teacher has not prepared a mature and clear assessment. The theoretical implications of this research can add scientific information related to lesson planning in the implementation of the independent curriculum. The practical implications of this research are as input for teachers and prospective teachers in carrying out effective planning in accordance with the independent curriculum procedures in order to achieve the expected goals.